(untitled) (Journal of Philosophy Culture and Political Science, 2015)
Aga Khan is active globally Institute, which is one of the historic receiver of Ismaili sect known since the Middle Ages for its terrorist activity, requires careful study. Formed as one of the areas of Shiite Islam, Ismaili Aga Khan in further has changed its altered form of ceremonial rituals and beliefs and have received the support of some international organizations. This organization has attracted the attention of the world community through charitable and educational outreach programs in many countries, mainly in developing countries and in mountainous regions. Having a central office in France Aga Khan Ismaili are engaged in large-scale organization of religious and social activities. Recently, apart from religious activities, there is activity in the social, political, economic directions. Key words: Shiites, Ismailis, Aga-Khan, imamate, ahlul-bayt.